Evaluation of the viscosity profile obtained for dispersions containing different proportions of milk protein concentrate / whey protein concentrate during simulated conditions of thermal processing. Issue 2 (December 2015) - Souza, Alisson Borges de; Costa, Luiz Carlos Gonçalves; Stephani, Rodrigo; Oliveira, Marcone Augusto Leal de; Perrone, Ítalo Tuler; Costa, Renata Golin Bueno
Abstract Denaturation and interaction of different proteins occur in different forms and intensity when the pH value varies in accordance with the medium in which they are located. This study aimed to verify the influence of whey protein/casein interaction in the evolution of viscosity at different pH values, using the Rapid Viscosity Analyzer (RVA) as the thermal processing simulator. Samples of commercial whey protein concentrate (WPC) and milk protein concentrate (MPC) have been analyzed. The results of this study can be applied in the development of products obtained from dairy powders such as processed cheeses and yoghurt.